Alcohol Consumption during Pregnancy and its association with Fetal Outcome in a Mountainous District of Nepal - Paudel, Rashmi; Pachya, Ambika Thapa; Maharjan, Muna; Napit, Krishtee; Poudyal, Amod Kumar (Journal of Karnali Academy of Health Sciences, 2022)
Background: Alcohol use during pregnancy has a negative health impact on pregnancy outcomes. There are inconsistencies in the relationship between alcohol consumption and outcomes in different scenarios. The studies done in Nepal on alcohol consumption have not looked for the consequences of alcohol consumption on pregnancy outcomes. Hence, this study assessed the maternal alcohol consumption practice and its effect on birth in the Sindhupalchowk district.Methods: Facility-based analytical study was conducted in nine health facilities with delivery services in Sindhupalchowk. Face-to-face interviews were done with 250 newly delivered mothers at the health facilities using pretested semi-structured questionnaire. Descriptive, logistic regression analyses were done. Participation was voluntary, and written informed consent was taken.Results: The study showed the prevalence of alcohol consumption during pregnancy among the newly delivered mothers was 35.6% (29.70 - 41.40). Among the study participants, four (1.6%) had stillbirths. Most of them (82.4%) had of normal birth weight. Low and moderate alcohol consumption was not seen to be significantly associated with low birth weight. However, its risk was seven times more in heavy drinking mothers and nine times among binge drinkers than non-drinkers.Conclusions: One out of three mothers consumed alcohol during pregnancy. Risk of low-birth-weight babies was highest with binge drinking during pregnancy. The most commonly consumed type of alcohol was Jaand which has cultural roots. Interventions to help mothers avoid alcohol consumption must be based on the cultural context, and local stakeholders and beneficiaries should be sensitized to the harm alcohol cause especially during pregnancy.